Suicide and suicidal behaviour - Turecki, Gustavo; Brent, David A (The Lancet (British edition), 2016)
Suicide is a complex public health problem of global importance. Suicidal behaviour differs between sexes, age groups, geographic regions, and sociopolitical settings, and variably associates with different risk factors, suggesting aetiological heterogeneity. Although there is no effective algorithm to predict suicide in clinical practice, improved recognition and understanding of clinical, psychological, sociological, and biological factors might help the detection of high-risk individuals and assist in treatment selection. Psychotherapeutic, pharmacological, or neuromodulatory treatments of mental disorders can often prevent suicidal behaviour; additionally, regular follow-up of people who attempt suicide by mental health services is key to prevent future suicidal behaviour.